The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1051/0004-6361/201833943
|View full text |Cite
|
Sign up to set email alerts
|

Ratio of black hole to galaxy mass of an extremely red dust-obscured galaxy at z = 2.52

Abstract: We present a near-infrared (NIR) spectrum of WISE J104222.11+164115.3, an extremely red dust-obscured galaxy (DOG), which has been observed with the Long-slit Intermediate Resolution Infrared Spectrograph (LIRIS) on the 4.2m William Hershel Telescope. This object was selected as a hyper-luminous DOG candidate at z ∼ 2 by combining the optical and IR photometric data based on the Sloan Digital Sky Survey (SDSS) and Wide-field Infrared Survey Explorer (WISE), although its redshift had not yet been confirmed. Bas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 66 publications
7
19
0
Order By: Relevance
“…This evolution fits that of the system WISE J104222.11+164115.3 (Matsuoka et al 2018) discussed above. This appears to be in the blowout phase, which would normally require its SMBH mass M 10 11 M to be close to Mσ.…”
Section: Smbh Growth In Evolving Galaxiessupporting
confidence: 84%
See 1 more Smart Citation
“…This evolution fits that of the system WISE J104222.11+164115.3 (Matsuoka et al 2018) discussed above. This appears to be in the blowout phase, which would normally require its SMBH mass M 10 11 M to be close to Mσ.…”
Section: Smbh Growth In Evolving Galaxiessupporting
confidence: 84%
“…The SMBH in NGC 1600 is significantly below it for any spin rate, and this is probably true of NGC 4889 (cf King 2016). A contender for the most extreme system is currently the very dust-obscured WISE J104222.11+164115.3, at redshift z = 2.52 (Matsuoka et al 2018). This galaxy has strongly blueshifted oxygen lines corresponding to an outflow velocity ∼ 1100 km s −1 , close to the prediction in Equation 2.…”
Section: Smbh Mass Evolutionmentioning
confidence: 56%
“…A low Eddington ratio in W0533−3401, for instance λ Edd < 0.3, seems not likely, otherwise M BH /M ⋆ of W0533−3401 will be higher than 0.2. Even if taking λ Edd = 1.0, the inferred M BH /M ⋆ of W0533−3401 is not only over one order of magnitude higher than the typical values ∼ 0.0002 − 0.0005 in the local Universe (Kormendy & Ho 2013), but also ∼ 5 times higher than the expected value by the evolutionary trend of M BH /M ⋆ (McLure et al 2006;Peng et al 2006;Merloni et al 2010;Targett et al 2012;Bongiorno et al 2014;Matsuoka et al 2018). We derive the black hole mass growth rateṀ BH of W0533−3401 from the bolometric luminosity by using the relation L AGN = (ηṀ BH c 2 )/(1 − η) and adopting η 1−η = 0.1.…”
Section: Rapid Growth Of Both the Stellar Component And The Central Smbhmentioning
confidence: 85%
“…We have confirmed that the choice of cutoff wavelength does not significantly affect the following results. Table 1 lists the detailed parameter ranges adopted in the SED fitting (see also Matsuoka et al 2018;Chen et al 2019;Toba et al 2019). In addition to the energy balance between UV/optical and IR part, CIGALE takes into account the balance between IR and radio luminosity that is parameterized by q IR , which are eventually an essential framework in CIGALE.…”
Section: Sed Modeling With Cigalementioning
confidence: 99%
“…The mean values of E(B −V ) * of the SDSS-and HSC-level objects are ∼0.19 and ∼0.45, respectively. Indeed, 5 HSC-level objects with mean E(B − V ) * of 0.45 satisfies a criterion of IR-bright dustobscured galaxies with S/N > 3 at 22 µm (see e.g.,Toba et al 2015; Toba & Nagao 2016; Toba et al 2017aToba et al , 2018Noboriguchi et al 2019).…”
mentioning
confidence: 99%